Perception et interprétation des émotions dans le débat radiodiffusé par les étudiants avancés de philologie romane - Bernadeta Wojciechowska (Studia Romanica Posnaniensia, 2015)
The article focuses on the French philology students’ skills of interpreting emotions in radio debates. Data analysis was conducted with the use of the interactional approach, discourse analysis and the rhetorical argumentation approach. The aim was to better understand the students’ interpretative actions and especially, their perception of ethos and pathos. The second objective of the study was to conduct a pilot test of the methodology inspired by research on argumentation in discourse in order to analyze persuasive discourse in a foreign language.